Microbial co-culturing strategies for fructo-oligosaccharide production - Castro, Cristiana C. (2019)
Fructo-oligosaccharide (FOS) mixtures produced by fermentation contain large amounts of non-prebiotic sugars. Here we propose a mixed culture of Aureobasidium pullulans and Saccharomyces cerevisiae cells to produce FOS and consume the small saccharides simultaneously, thereby increasing FOS purity in the mixture. The use of immobilised A. pullulans in co-culture with encapsulated S. cerevisiae, inoculated after 10h fermentation, enhanced FOS production in a 5L bioreactor. Using this strategy, a maximal FOS concentration of 119g L1, and yield of 0.59gFOS gsucrose1, were obtained after 20h fermentation, increasing FOS productivity from about 4.9 to 5.9gFOS L1h1 compared to a control fermentation of immobilized A. pullulans in monoculture. In addition, the encapsulated S. cerevisiae cells were able to decrease the glucose in the medium to about 7.6% (w/w) after 63h fermentation. This provided a final fermentation mixture with 2.0% (w/w) sucrose and a FOS purity of over 67.0% (w/w). Moreover, a concentration of up to 58.0g L1 of ethanol was obtained through the enzymatic transformation of glucose. The resulting pre-purified FOS mixture could improve the separation and purification of FOS in downstream treatments, such as simulated moving bed chromatography.